Pharmacological studies on Jatropha curcas as a possible source of anti-arrythmic (Beta-blocker) agent - Fojas, Felicita R.; Garcia, L.L; Venzon, E.L; Villanueva, B.A; Fojas, A.J; Llave, I. (1986)
Preliminary pharmacological studies of Jatropha curcas Linn. or "tubang bakod" leaves suggest that this plant has potent cardiovascular action and is a possible source of an anti-arrhythmic (beta blocker) agent. Experiments on guinea pig showed decreased heart force (negative inotropic), decreased heart rate (negative chronotropic) and blocking of the isoprenaline stimulation responses on the auricle which is somewhat similar to a well-known beta-blocker, propranolol. Other findings indicate that the plant is a central depressant with some sympathomimetic activity and a potent drug with LD50 values of: 24.5 g/kg (18.15 g/kg - 33.08 g/kg) and 750 mg/kg (517 mg/kg - 1087 mg/kg), for the acqueous extract (decoction) and methanol extract, respectively.